2021
DOI: 10.1097/ju.0000000000001342
|View full text |Cite|
|
Sign up to set email alerts
|

Discrepancies in the Recommended Management of Adrenal Incidentalomas by Various Guidelines

Abstract: Adrenal incidentalomas are being discovered with increasing frequency, and their discovery poses a challenge to clinicians. Despite the 2002 National Institutes of Health consensus statement, there are still discrepancies in the most recent guidelines from organizations representing endocrinology, endocrine surgery, urology and radiology. We review recent guidelines across the specialties involved in diagnosing and treating adrenal incidentalomas, and discuss points of agreement as well as controversy among gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 27 publications
0
32
0
1
Order By: Relevance
“…On the other hand, adrenal gland tumors found by chance during a physical examination or over the course of various diseases are collectively called adrenal incidentalomas. 5 The prevalence of adrenal incidentaloma approaches 3% in middle age but increases to as much as 10% in the elderly. 6 Of the adrenal incidentalomas with a pathological diagnosis, adrenal malignancies account for only 10% 7,8 but rapid developments in diagnostic imaging techniques, such as abdominal ultrasonography, computed tomography, and magnetic resonance imaging, have increased chances to find these rare tumors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, adrenal gland tumors found by chance during a physical examination or over the course of various diseases are collectively called adrenal incidentalomas. 5 The prevalence of adrenal incidentaloma approaches 3% in middle age but increases to as much as 10% in the elderly. 6 Of the adrenal incidentalomas with a pathological diagnosis, adrenal malignancies account for only 10% 7,8 but rapid developments in diagnostic imaging techniques, such as abdominal ultrasonography, computed tomography, and magnetic resonance imaging, have increased chances to find these rare tumors.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, adrenal gland tumors found by chance during a physical examination or over the course of various diseases are collectively called adrenal incidentalomas 5 . The prevalence of adrenal incidentaloma approaches 3% in middle age but increases to as much as 10% in the elderly 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Since adrenalectomies usually account for a small part of a laparoscopic surgeon's practice, it has been suggested that LA should be performed in specialized centers only, by advanced laparoscopy experts and in a context of multidisciplinary management. 33 Moreover, the laparoscopic technique hampers the surgeon's ability to receive tactile feedback, which is traditionally used to discern tumor edges and identify vascular structures in open procedures. In addition, the retroperitoneal space is narrow and barely reachable by laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Varying approaches to endocrine testing have been described. Shenoy et al suggest endocrine screening for patients at high risk of associated endocrine dysfunction (hypertension, diabetes, pre-diabetes, young age, bilateral adrenal myelolipomas) [9], while Maas et al recommend hormonal screening of all incidentalomas with plasma free metanephrines, urinary fractionated metanephrines, and 1 mg dexamethasone suppression test [22].…”
Section: Discussionmentioning
confidence: 99%